GEOMETRY DESIGN AND ANALYSIS OF AN ELECTRIC BUS FOR THE INTERIOR THER-MAL MODELLING - Nițucă, Costică; Chiriac, Gabriel; Nucă, Ilie; Cazac, Vadim; Burduniuc, Marcel (Journal of Energy Technology, 2023)
The heating, ventilation and air-conditioning (HVAC) system represents the main auxiliary load for any type of bus. Being the most significant energy-consuming auxiliary load for the electric us, it must be given special attention in an electric bus system design. To study the heat transfer and thermal optimization for passenger comfort in the electric bus computer-aided design (CAD) is used. The geometry of an electric bus interior is designed considering the main components of the vehicle: passenger cabin, driver’s cabin, windows, walls, and seats. Materials of the same type as those used in the real bus are considered for the geometry model. Based on the heat transfer theory, a thermal model and simulations are made for the heat transfer inside the elec- tric bus. The simulated data are compared with measurement data, and based on these, it can be concluded that the thermal model of the electric bus can be validated and used further for a wide variety of thermal simulation types.